Impact of winter conditions on wind erosion susceptibility of clay soils - Josef Kučera; Martin Blecha; Jana Podhrázská; Jan Szturc; Petra Fukalová; Hana Středová (Soil and Water Research, 2024)
Wind erosion primarily affects sandy soil in arid areas.  However, the specific winter meteorological conditions (freeze-thaw cycles) lead to the disintegration of aggregates into erosion-risk fractions even on clay soils. These changes in the winter erodibility of clay soils were investigated in an area with frequent occurrences of wind erosion in southeastern Moravia (Czech Republic, Central Europe) between the years 2014/2015 and 2020/2021.  The percentage of non-erodible fraction (NEF) before and after winter was assessed. NEF was set as particles larger than 0.84 mm and also larger than 2.00 mm (based on field observations), while soils containing less than 40% NEF have the highest susceptibility to wind erosion. Autumn NEF0.84 content was 80 and 95%, indicating significant resistance to wind, and although there was a significant decrease in spring to 65%, it still exceeded the 40% threshold. Autumn NEF2.00 content of 60-70% also indicates a significant resistance to wind erosion. However, spring values were well below the 40% threshold (8 to 35%), indicating significant susceptibility to wind erosion. It showed a significant negative influence of winter on NEF2.00 content and, thus, a greater susceptibility to erosion in spring compared to NEF0.84. Our results also document vegetation efficiency on the presence of NEF.